A modified model for wet gas flowrate measurement considering entrainment downstream of a cone meter. (March 2021) - Zhao, Fan; Li, Shanshan; Zheng, Xuebo; He, Denghui; Bai, Bofeng
Abstract: To develop a reliable wet gas flowrate measurement model, the relationships between pressure drop characteristics and entrainment downstream of the cone are investigated experimentally. The equivalent diameter ratio of the cone is 0.45. The experimental fluids are air and tap water with X LM in the range of 0–0.3. The two-phase mass flow coefficient and pressure loss ratio are employed to establish the measurement model. The piecewise characteristics of pressure loss ratio are disclosed innovatively, which is explained by the different intensity of entrainment downstream of cone caused by gas-liquid jetting. A simplified method for evaluating the degree of entrainment is proposed to facilitate the establishment of the modified measurement model. Under the present experimental conditions, the relative error of liquid fluctuates within ±20% when X LM is larger than 0.02, and the relative error of gas flowrate is within ±5%. Compared with the model without piecewise consideration, the relative error of the liquid flowrate of the modified model reduces obviously under low wetness conditions (0.02< X LM <0.1). The modified measurement model provides a reliable and cost-effective technology for wet gas flowrate measurement. Highlights: The piecewise characteristics of the pressure loss ratio are disclosed and analyzed based on visualization. The liquid layer thickness upstream of the cone is calculated to facilitate establishing the modified model. The modified model improves the prediction accuracy under low wetness conditions.